Upregulation of microRNA-137 expression by Slug promotes tumor invasion and metastasis of non-small cell lung cancer cells through suppression of TFAP2C - Chang, Tzu-Hua; Tsai, Meng-Feng; Gow, Chien-Hung; Wu, Shang-Gin; Liu, Yi-Nan; Chang, Yih-Leong; Yu, Sung-Liang; Tsai, Hsing-Chen; Lin, Shih-Wen; Chen, Yen-Wei; Kuo, Po-Yen; Yang, Pan-Chyr; et al. (Cancer letters, 2017)
The epithelial-mesenchymal transition (EMT) regulator, Slug, plays multifaceted roles in controlling lung cancer progression, but its downstream targets and mechanisms in promoting lung cancer progression have not been well defined. In particular, the miRNAs downstream of Slug in non-small cell lung cancer (NSCLC) remain undetermined. Here, we report that miR-137 is downstream of the EMT regulator, Slug, in lung cancer cells. Slug binds directly to the E-box of the miR-137 promoter and up-regulates its expression in lung cancer cells. Knockdown of miR-137 abolished Slug-induced cancer invasion and migration, whereas upregulation of miR-137 was found to trigger lung cancer cell invasion and progression by direct suppressing TFAP2C (transcription factor AP-2 gamma). Clinical data showed that lung adenocarcinoma patients with low-level expression of Slug and miR-137 but high-level expression of TFAP2C experienced significantly better survival. miR-137 is a Slug-induced miRNA that relays the pro-metastatic effects of Slug by targeting TFAP2C. Our findings add new components to the Slug-mediated regulatory network in lung cancer, and suggest that Slug, miR-137, and TFAP2C may be useful prognostic markers in lung adenocarcinoma. •miR-137 is a Slug-induced miRNA in lung cancer cells.•Knockdown of miR-137 abolishes Slug-induced cancer cell invasion and migration.•miR-137 functions as an oncogene in lung cancer.•Slug-induced miR-137 enhances lung cancer progression by direct targeting TFAP2C.•Our findings add new components to the Slug regulatory network in lung cancer.